Comportamento de compra on-line de adolescentes das escolas públicas e privadas de Santana do Livramento/RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
E-commerce has become an important tool for buying and selling relationships. This type of tool can be used by various audiences, regardless of social class, age, race or religious beliefs. In view of this, this work seeks to identify the behavior of online purchases of a specific population, who are adolescents from public and private schools of Sant'Ana do Livramento/RS. The research is descriptive, because it interprets the reality of adolescents without intending to modify it. The research approach is quantitative, which uses statistical methods to quantify the behavior of the public investigated. The instrument for data collection was applied personally in the participating schools, through a questionnaire with closed questions, through authorization terms of the students and those in charge. A total of 145 responses were obtained, of which 125 are public schools and 20 are private schools. The questionnaires were applied in 11 public schools and 2 private high schools in the municipality. The results were analyzed through statistical data, using Excel and SPSS software. In view of this, it was observed that the behavior of public and private school consumers in Sant'Ana do Livramento show many similarities. The results of the survey showed small differences between the behavior of public and private school students. The means of the two types of students did not present a sufficient level of significance to explain the behavior of the adolescents. The implications of this study will be very important for the scientific knowledge regarding the behavior of the adolescent consumer and for the understanding of the companies on the behavior of the local adolescent consumers.
Keywords: Administração; Comportamento do consumidor: adolescente; Comércio eletrônico; E-commerce; Shopping behavior: teenagers; CNPQ::CIENCIAS SOCIAIS APLICADAS